Puberty Predicts Approach But Not Avoidance on the Iowa Gambling Task in a Multinational Sample - Icenogle G. (2017)
© 2016 The Authors. Child Development © 2016 Society for Research in Child Development, Inc. According to the dual systems model of adolescent risk taking, sensation seeking and impulse control follow different developmental trajectories across adolescence and are governed by two different brain systems. The authors tested whether different underlying processes also drive age differences in reward approach and cost avoidance. Using a modified Iowa Gambling Task in a multinational, cross-sectional sample of 3,234 adolescents (ages 9–17; M = 12.87, SD = 2.36), pubertal maturation, but not age, predicted reward approach, mediated through higher sensation seeking. In contrast, age, but not pubertal maturation, predicted increased cost avoidance, mediated through greater impulse control. These findings add to evidence that adolescent behavior is best understood as the product of two interacting, but independently developing, brain systems.